(untitled) (Advances in Applied Biological Research, 2024)
This paper deals with the Ethno medicinal treatment practices for treating different types of ailments. The present survey comprises of totally fifty Ethno-medicinal formulae which provides information in detail on the therapeutic values of 34 plant species belonging to 31 genera and 24 families, covering 21 different ailments or health exigencies. Information on botanical names, vernacular names, families, plant parts & used methods of preparation of drugs as well administration are presented in a detailed manner. The Information collected in this study would act as vital data for scientific community.